In Manipur… Horticulture making farmers prosperous - Roy, SS; Devi, Ch. Basudha; Ansari, MA; Sailo, B; Sharma, S K; Punitha, P; Prakash, N; Ngachan, S V (Indian Horticulture, 2019)
The success stories indicates that horticulture-based integrated farming system has evolved successfully to meet the need in a way that combines the essential requirements of productivity, profitability and sustainability, because it encompasses year-round food production alongside conservation of natural resources. Adoption of horticulture-based integrated farming system always emphasizes the shift from commodity-based to resource-based planning, ensuring ecological and economic access to food and nutrition to the farm households with improved resource-use efficiency.